The PFA-100 cannot detect blood group-dependent inhibition of platelet function by eptifibatide or abciximab at therapeutic plasma concentrations - Feuring, Martin; Ruf, A.; Schultz, Armin; Wehling, Martin (Platelets, 2010)
Previous investigations revealed that AB0 blood groups are associated with divergent concentrations of several coagulation factors. Concentrations of von Willebrand factor (vWF) and factor VIII are lower in individuals with blood group 0 compared to subjects with blood group A, B or AB, which might in turn result in a reduced inhibition of platelet aggregation in individuals with blood group 0. The aim of the present in vitro investigation was to elucidate the impact of AB0 blood group-dependent vWF concentrations on eptifibatide and abciximab mediated inhibition of GPIIb/IIIa function. Platelet function was measured with the platelet function analyzer PFA-100® at baseline and at increasing concentrations of eptifibatide and abciximab. It was stratified for blood group 0 vs A. If measured with the collagen/ADP cartridge, blood group 0 was associated with a prolonged mean baseline closure time in comparison with blood group A (94.3 ± 14.6 s vs. 74.6 ± 9.9 s, p = 0.007) which was paralleled by reduced concentrations of vWF and factor VIII. In contrast, no statistically significant differences in closure times (167.4 ± 83.9 s vs. 140.1 ± 99.0 s, p = 0.562) could be found in the presence of eptifibatide (0.1 µg/ml). Higher concentrations of abciximab (1 µg/ml) than those of eptifibatide were needed to increase the closure times in both cartridges of the PFA-100, but at this concentration of abciximab differences in closure times could not be detected most probably due to higher variability at these drug concentrations. The PFA-100® is not suitable for monitoring abciximab or eptifibatide within the therapeutic concentration range because the highest concentrations where the PFA-100® had measurable closure times of below 300 s is much too low to lead to the necessary platelet inhibition and, consequently, does not resemble the in vivo situation.
Gesehen am 04.12.2023